2014
DOI: 10.5935/0004-2749.20140058
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the horizontal corneal diameter, central corneal thickness, and axial length in premature infants

Abstract: Purpose: To determine the horizontal corneal diameter, central corneal thickness, and axial length in premature infants. Methods: Infants with a birth weight of less than 2,500 g or with a gestation period of less than 36 weeks were included in the study. Infants with retinopathy of prematurity (ROP) were allocated to Group 1 (n=138), while those without ROP were allocated to Group 2 (n=236). All infants underwent a complete ophthalmologic examination, including corneal diameter measurements, pachymetry, biome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(20 reference statements)
2
3
0
Order By: Relevance
“…We previously investigated the axial length of 374 eyes in 187 premature infants at 40 weeks of mean postmenstrual age and reported that there were no differences in axial length between infants with and without ROP (19). In the present study we achieved similar results, except for infants between 34 and 37 weeks postmenstrual age.…”
Section: Discussionsupporting
confidence: 83%
“…We previously investigated the axial length of 374 eyes in 187 premature infants at 40 weeks of mean postmenstrual age and reported that there were no differences in axial length between infants with and without ROP (19). In the present study we achieved similar results, except for infants between 34 and 37 weeks postmenstrual age.…”
Section: Discussionsupporting
confidence: 83%
“…Studies on corneal development are also inconsistent when reporting how long is needed for corneas to mature ( 13 ). Ozdemir et al ( 14 ) believed that the horizontal corneal diameter of normal newborns was 10–10.5mm, which increased by 0.15–1.0mm at the end of one year; this study's results support this. Nanda ( 15 ) believed that the corneal diameter of infants 6–12 months old could approach the normal adult diameter of 11.80mm.…”
Section: Discussionsupporting
confidence: 79%
“…These authors obtained a mean axial length between 16.37 and 16.66 mm, anterior chamber depth between 2.14 and 2.26, posterior segment length between 10.18 and 10.47, and lens thickness between 3.93 and 4.04 mm. Similarly, we have previously reported the mean anterior chamber depth as 2.1 ± 0.4 mm, lens thickness as 4.1 ± 0.7 mm, vitreous length as 10.3 ± 1.5 mm, and axial length as 16.4 ± 1.3 mm in 138 eyes of 69 premature infants with ROP (27) . In the present study, the anterior chamber depth, vitreous length, and axial length were slightly greater in boys than girls.…”
Section: Discussionmentioning
confidence: 99%